Tunable superhydrophobic titanium nitride surface by ultrafast laser processing. Issue 24 (15th December 2022) - Radhakrishnan, J.; Diaz, M.; Cordovilla, F.; Ocaña, José L.
Abstract: The interaction of water droplets to the engineered hierarchical surface structures depends on the synergy between the topographical and chemical modifications. In this work, we develop an ultrafast laser processing technology to create a robust superhydrophobic nanostructured titanium nitride (TiN) surface. The process is based on the manipulation of the surface geometry and the low-pressure technique's accelerated adsorption of Volatile Organic Compounds (VOC). The laser-processed surfaces are composed of nanoscale geometry overlapped with porous, spongy structures. The metal oxides formed on the TiN surface were hydrophilic and subjected to accelerated VOC adsorption by low-pressure technique via condensation reaction with surface hydroxyl groups formed by heterolytic adsorption of water molecules from the environment. The decrease of surface energy due to the presence of adsorbed hydrocarbons and the topography of the nanostructures allow the trapping of small volumes of air. The presence of a layer of air favour the Cassie-Baxter state of wetting state. Static contact angles ranging from 155 to 180° have been reached depending on the geometry of the nanostructures. A comparative study of vacuum processed and aged (15 days) samples under atmospheric conditions were also performed. The chemical analysis by XPS demonstrates that the water molecules attached to hydroxyl groups passivate these reactive sites and hinder the adsorption of VOC, decreasing the adsorption rate drastically under aging in atmosphereic conditions. In contrast, it is enhanced under low-pressure conditions due to the reduced amount of water vapour.